An Introduction to the AI Special Issue and a Modern Framework for AI in Sport Management - Jun Woo Kim; Vitaly Ford (Journal of Applied Sports Management, 2025)
This paper introduces the special issue while also exploring the theoretical foundations and practical applications of AI in sport management, guided by Artificial Intelligence: A Modern Approach (Russell & Norvig, 2021). The manuscript examines AI’s evolution from rule-based systems to large language models (LLM)–driven intelligent agents and classifies the technology into five major subfields—machine learning, natural language processing, computer vision, reinforcement learning, and AI agency. Using real-world sport industry examples and recent academic research, this paper presents a modern taxonomy of AI’s role in sport management, articulates managerial implications, and outlines future research directions necessary for sustainable and ethical integration of AI in sport organizations.
Keywords: artificial intelligence (AI); large language models (LLMs); AI agent